Numerical Simulation of Ethanol Air Diffusion Flame Quenching under Transverse AC Electric Field - Shuai Zhao; Boyun Liu; Bo Zhao; Taiwei Li; Qi Shu (Fire, 2022)
The electric field fire extinguishing technology is an efficient, clean, and new fire extinguishing technology that can be operated at a long distance. In order to study the synergistic mechanism of “electric-flow-heat” in the process of transverse AC electric field fire extinguishing, the ionic wind formed by the influence of electric field on each charged particle during the burning process of ethanol–air diffusion flame is simulated by the non-premixed combustion model, and the experimental phenomenon of flame quenching in the transverse AC electric field is reproduced by means of numerical simulation. The accuracy of the numerical model was verified by comparing the temperature and flow velocity in the region obtained from the simulation with the data measured in the experiment. According to both simulated and experimental phenomena, we present a hypothesis of how the flame is quenched under the influence of an electric field. The next research directions are: (1) improving the accuracy of numerical simulation by building fine models; (2) studying the dynamic mechanism of real flames by particle image velocimetry technology.